The organization of myosin and actin in rapid frozen nerve growth cones (The Rockefeller University Press, 1989)
Rapid freezing and freeze substitution were used in conjunction with immunofluorescence, whole mount EM, and immunoelectron microscopy to study the organization of myosin and actin in growth cones of cultured rat superior cervical ganglion neurons. The general cytoplasmic organization was determined by whole mount EM; tight microfilament bundles formed the core of filopodia while a dense meshwork formed the underlying structure of lamellipodia. Although the central microtubule and organelle-rich region of the growth cone had fewer microfilaments, dense foci and bundles of microfilaments were usually observed. Anti- actin immunofluorescence and rhodamine phalloidin staining of f-actin both showed intense staining of filopodia and lamellipodia. In addition, staining of bundles and foci were observed in central regions suggesting that the majority of the microfilaments seen by whole mount EM are actin filaments. Anti-myosin immunofluorescence was brightest in the central region and usually had a punctate pattern. Although less intense, anti-myosin staining was also seen in peripheral regions; it was most prominent at the border with the central region, in portions of lamellipodia undergoing ruffling, and in spots along the shaft and at the base of filopodia. Immunoelectron microscopy of myosin using postembedment labeling with colloidal gold showed a similar distribution to that seen by immunofluorescence. Label was scattered throughout the growth cone, but present as distinct aggregates in the peripheral region mainly along the border with the central region. Less frequently, aggregates were also seen centrally and along the shaft and at the base of filopodia. This distribution is consistent with myosins involvement in the production of tension and movements of growth cone filopodia and lamellipodia that occur during active neurite elongation.